2019
DOI: 10.1016/j.jneuroim.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Propofol reduces microglia activation and neurotoxicity through inhibition of extracellular vesicle release

Abstract: A B S T R A C TPropofol is an established anesthetic widely used for induction and maintenance of anesthesia. We investigated propofol for its anti-inflammatory effects on microglia and found that propofol treatment is associated with substantial lower levels of extracellular vesicles (EVs) in immune activated microglia. Importantly, EVs collected from immune activated microglia reversed propofol-mediated anti-inflammatory and neuroprotective effects, suggesting that propofol reduces proinflammatory microglia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Propofol, as one of the most commonly used IV drugs for the anesthesia induction and maintenance during surgical procedures and critical care sedation in ICUs, has been reported to have potential therapeutic effects on various neurological disorders including neurodegenerative diseases (Shao et al, 2014), stroke (Hausburg et al, 2020), and depression (Mickey et al, 2018). Here, our results, together with our previous study (Liu et al, 2019), have demonstrated the anti-inflammatory roles of propofol in both microglial cell line and primary microglia. Our findings match with the results obtained from various in vitro and in vivo studies, implying propofol as a promising drug candidate in treating neuroinflammation and its related diseases (Peng et al, 2014;Liu et al, 2017;Luo et al, 2018;Wu Q. et al, 2018;Zheng et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Propofol, as one of the most commonly used IV drugs for the anesthesia induction and maintenance during surgical procedures and critical care sedation in ICUs, has been reported to have potential therapeutic effects on various neurological disorders including neurodegenerative diseases (Shao et al, 2014), stroke (Hausburg et al, 2020), and depression (Mickey et al, 2018). Here, our results, together with our previous study (Liu et al, 2019), have demonstrated the anti-inflammatory roles of propofol in both microglial cell line and primary microglia. Our findings match with the results obtained from various in vitro and in vivo studies, implying propofol as a promising drug candidate in treating neuroinflammation and its related diseases (Peng et al, 2014;Liu et al, 2017;Luo et al, 2018;Wu Q. et al, 2018;Zheng et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…Propofol acts by potentiating the γ-aminobutyric acid type A (GABA A ) receptormediated inhibitory tone in the CNS (Marik, 2004). Interestingly, our group, together with other labs, have reported that propofol is able to modulate the phenotype of BV2 microglial cells and assert anti-inflammatory effects (Luo et al, 2018;Wu Q. et al, 2018;Zheng et al, 2018;Liu et al, 2019). Similar results were obtained when primary microglia were treated with propofol (Peng et al, 2014).…”
Section: Introductionsupporting
confidence: 68%
“…Yu et al [ 6 ] revealed that propofol inhibited the microglial phagocytosis under increase pressure circumstance. In addition, Liu and his colleagues found that propofol can suppress microglial activity, including phagocytosis ability, in response to lipopolysaccharide (LPS) exposure [ 9 ]. However, there is currently limited evidence regarding the effect of a single administration of propofol on resting microglia, i.e., in the absence of activation-inducing insult.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol, a widely used short-acting intravenous sedative agent used in clinical practice, is often selected for general anesthesia or sedation of patients receiving surgery or undergoing diagnostic procedures [ 7 ]. Evidence has indicated that propofol can attenuate microglial responses when cells are exposed to external stimuli [ 8 , 9 ]. It can inhibit pressure-stimulated macrophage phagocytosis via the GABA A receptor [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Propofol induces the anti-inflammatory treatment by suppressing microglial activation after CA and TNF-α and IL-1β release, likely via the purinergic ligand-gated ion channel 7 receptor (P2X7R)/phosphor-p38 (p-p38) pathway [117]. Another study shows propofol might reduce microglia activation and neurotoxicity by inhibiting extracellular vesicle release [118]. These shreds of evidence suggest that propofol may be a new treatment for neuroinflammation after CA.…”
Section: Propofolmentioning
confidence: 99%